Beyond the obvious: unveiling primary effusion lymphoma in a 76-year-old female with multifaceted clinical presentation - Kambampati, Sailaja; Tourani, Vijaya; Jain, Saurabh (International Journal of Research in Medical Sciences, 2023)
Primary effusion lymphoma (PEL) is an exceptionally rare and challenging entity to diagnose, characterized by the development of lymphomatous effusions in body cavities without a solid tumour mass. Here, we present a case of PEL in a 76-year-old retired professor with a complex medical history including diabetes, hypertension, and bilateral total knee replacement surgery. The patient initially presented with dry cough and breathlessness, which led to the discovery of a right pleural effusion exhibiting lymphocytic predominance with high ADA but lacking malignant cells. Prompt initiation of empiric anti-tubercular therapy (ATT) resulted in symptomatic improvement and resolution of the effusion. However, subsequent admission to the emergency room due to vomiting, weakness, and walking difficulties unveiled a positive rapid antigen test for COVID-19 and identified moderate right-sided pleural effusion. Additional investigations including positron emission tomography–computed tomography (PET-CT), magnetic resonance imaging (MRI) brain, and cell block analysis unveiled intriguing findings, prompting further evaluation and immunohistochemical (IHC) analysis. IHC markers revealed CD20+, Ki-67 proliferation index of 80%, CD79a+, CD 3 -, CD138-, CD30-, and CD10-, indicative of atypical B cell proliferation. Importantly, the presence of human herpes virus-8 (HHV-8) was confirmed through LANA1 staining, solidifying the diagnosis of primary effusion lymphoma. This case highlights the diagnostic challenges encountered and emphasizes the importance of comprehensive evaluation and IHC profiling confirmation in establishing an accurate diagnosis of PEL.